Dynamics of the Trade Balance and the Terms of Trade: The J-Curve? - Backus, David K.; Kehoe, Patrick J.; Kydland, Finn E. (American Economic Review, 1994)
We provide a theoretical interpretation of two features of international data: the countercyclical movements in net exports and the tendency for the trade balance to be negatively correlated with current and future movements in the terms of trade, but positively correlated with past movements. We document the same properties in a two-country stochastic growth model in which trade fluctuations reflect, in large part, the dynamics of capital formation. We find that our general-equilibrium perspective is essential: the relation between the trade balance and the terms of trade depends critically on the source of fluctuations.